Influence of team members on nurses’ satisfaction with their own work - Terzic Markovic, Dragana; Rankovic Vasiljevic, Radmila (Nursing in the 21st Century, 2012)
INFLUENCE OF TEAM MEMBERS ON NURSES’ SATISFACTION WITH THEIR OWN WORK Introduction. Teamwork is essential to provide nursing care. Division of work among doctors, nurses and other health and non-health workers is needed, but none of the professional groups can provide complete health care by its individual work. Aim. Establish up to what level activities of the team members influence satisfaction of nurses with their own work. Methods. The research was done by type – sectional study, on the sample of 148 nurses. Specially designed questionnaire was created for the purpose of this survey. Results: According to the data, nurses completely cooperate with other nurses and always solve problem together (45.9%). Nurses generally receive assistance from a doctor in solving problems in 39.2% of cases. Obtained results that 79.1% of nurses is likely to continue working in the same hospital, are in favor of satisfaction with their own work; this is certainly also contributed by other members of the team. Conclusion. Building and maintaining relationships with colleagues and understanding the different needs of others are key factors for efficient teamwork. Results indicate the need to build better relationships and team work.